Making Markets Through Coalitions: The European Union and the Debate Over Ukraine's National Resources - Aron Buzogány; Mihai Varga (JCMS: Journal of Common Market Studies, 2024)
Abstract This article studies how the European Union (EU) influences the dynamics between supporters and opponents of market liberalization in partner countries. We focus on Ukraine's attempts to safeguard timber trade and agricultural land sales from international markets through moratoria before 2022. We find that the EU intervenes in domestic debates both directly and through domestic pro-market coalitions to frame these moratoria as expressions of `vested interests' and instances of state weakness. The EU effectively linked the free trade argument with protecting the environment (as the moratorium tolerated illegal logging) and human rights (as the land moratorium denied landowners their property rights). The EU thus fostered discourses and coalitions prioritizing liberalization over protectionist interests and environmental concerns. This article implies that the EU should encourage debates around market liberalization rather than de-legitimize opponents, as reconstruction in Ukraine following Russian aggression will require both EU assistance and broader internal coalitions.
Keywords: 330; constructivism; discursive institutionalism; external economic relations; international political economy; single market and monetary union; trade and investment policy